Hybrid Solar–Electric Kiln for Sustainable Timber Drying: Temperature Stabilization, Equilibrium Moisture Conditions, and Grid-Energy Savings Under a Temperate Winter Climate - Phonetip, Khamtan; BELLEVILLE, BENOIT; Chan, Leon (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
Solar kilns offer a low-operational cost alternative to conventional timber drying but suffer from weather-dependent temperature instability that limits industrial uptake. This study evaluated a 0.94 m³ hybrid solar–electric kiln prototype that combines passive solar gain with a thermostatically controlled 2 kW electric booster, with the aim of quantifying its temperature stabilisation, equilibrium moisture conditions, and grid-energy contribution under Melbourne winter conditions in Australia. Three solar-only and three hybrid trials (09:00–16:00, 50 °C setpoint) were conducted in July-August 2025 at the Burnley Campus, Richmond, Victoria (37.83 °S, 145.02 °E). Ambient temperature, relative humidity, and global horizontal irradiance were obtained from CERRA reanalysis and CAMS at five-minute resolution. Without auxiliary heat, the kiln temperature rose approximately10 °C above ambient on overcast days and reached the 50 °C setpoint only briefly on the sunniest day, fluctuating with the insolation. With auxiliary heating, the kiln reached the 50 °C setpoint within 15–30 min and was maintained at 50 ± 1 °C, approximately 25 % above the typical solar-only midday peak of 40 °C, and the kiln-air equilibrium moisture content (EMC) decreased from 6 % to 3 %. A linear regression of kiln temperature on ambient temperature, ambient relative humidity, and irradiance achieved R² = 0.70 on the training data. The hybrid system displaced 25–79 % of the heating energy that would otherwise have been drawn from the grid, expressed as a solar contribution fraction (SCF) relative to continuous heater operation. These results indicate that low-cost hybrid solar–electric kilns can deliver stable thermodynamic drying conditions while substantially reducing grid-energy demand, even in temperate winter climates.